Food Security: A Critical Analysis of Wheat Procurement, Transportation, and Storage Challenges in Punjab, Pakistan - Munib-ur-Rehman (Journal of Public Policy Practitioners, 2023)
This research aims to analyze food insecurity in Pakistan, with a specific focus on wheat crop within the Punjab province. It investigates the key issues, their causes, and proposes potential solutions to improve the overall effectiveness and efficiency of wheat procurement, transportation, and storage systems in Punjab. The study employed a mixed-methods approach incorporating field observation, data analysis, and questionnaires administered to district food controllers regarding the smuggling of wheat crop. Wheat procurement by the Punjab government was thoroughly analyzed and an overview of the wheat value chain is presented based on interviews with key informers, site visits, and observation. A cost-benefit analysis (CBA) was conducted to evaluate the viability of implementing grain storage silos in Punjab. The project is financially viable with a payback period of 5-6 years. Moreover, a survey of field officers was carried out to determine the scope and the determinants of wheat smuggling from Punjab. The findings of this research provide valuable information to policymakers, government agencies, and stakeholders in designing effective interventions to enhance food security and to address the specific challenges faced in the wheat sector of Punjab, Pakistan.